Effect of being fully-clothed in water on the distance between the centre of buoyancy and the centre of mass as well as pulmonary ventilation for people involved in water-related incidents - Watanabe, Y.; Moriyama, S.; Inagaki, R.; Wakayoshi, K. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
This study aimed to discover clothing`s effects on human pulmonary ventilation, buoyancy, and horizontal posture in water. Ten male university competitive swimmers were chosen as study participants. All assessments were conducted while participants were in the streamline posture, while centre of mass assessment was conducted on land, and buoyancy was assessed in both the Jammer swimsuit and fully clothed conditions. For the fully clothed condition, participants were asked to wear T-shirt and shorts. Judging from the assessment of distance between centre of buoyancy and centre of mass, clothing as defined by this study seemed to have no impact on participants` horizontal posture. Although no discrepancy was found in distance between centre of buoyancy and centre of mass, both of which indicate a horizontal posture, decreased pulmonary ventilation was observed in the fully clothed condition, resulting also in reduced buoyancy. Decreased pulmonary ventilation under the fully clothed condition suggested that clothing can affect human inspiration in water. This indicates to the possibility of clothing having some degree of impact on the human thorax`s movement as breathing becomes restricted, that is, more shallow.